Impact of shoe and cleat type on youth baseball pitching biomechanics. Issue 6 (3rd July 2022) - Gdovin, Jacob R.; Wade, Chip; Williams, Charles C.; Luginsland, Lauren A.; Wilson, Samuel J.; Garner, John C.
ABSTRACT: Shoulder and elbow injuries among baseball pitchers of various ages and abilities continue to rise despite exhaustive efforts analysing pitch type and count; however, it has yet been determined if footwear plays a role in altering pitching mechanics and subsequently injury susceptibility. Therefore, the purpose of the study was to investigate the effect footwear might have on youth baseball pitching mechanics. Data were collected on eleven youth baseball pitchers wearing two different shoes on two different surface inclinations. A repeated measures ANOVA was utilised to determine differences between upper and lower extremity joint kinematics and kinetics ( p < 0.05). Results indicate wearing moulded cleats elicited significantly greater amounts of shoulder internal rotation torque, angle and velocity as well as elbow varus torque. Turf shoes caused an increased plantarflexion joint angle in the stride leg ankle and shoulder external rotation torque, angle and velocity. The findings of this study suggest that the footwear worn by a youth baseball pitcher does alter the shoulder and elbow dynamics in the dominant throwing arm as well as the amount of ankle plantarflexion in the stride leg.